Folic-Acid-Modified Fe-TCPP Metal-Organic Frameworks as Sonosensitive Agents and siATAD3A Carriers for Sonodynamic Co-Gene-Ferroptosis Therapy in Triple-Negative Breast Cancer - Yang Du; Jiangnan Yang; Shuai Chen; Xiaoxin Yang; Yian Wang; Yiyuan Yang; Deyuan Fu (ACS Biomaterials Science & Engineering, 2026)
Abstract Triple-negative breast cancer (TNBC) represents the most aggressive form of breast cancer and is associated with the worst prognosis. Ferroptosis holds great promise as an emerging therapeutic strategy; however, TNBC cells demonstrate reduced sensitivity to ferroptosis as a result of elevated mitochondrial membrane potential (MMP), inadequate production of reactive oxygen species (ROS), and the presence of activated antioxidant defencses, making it difficult for lipid peroxidation to accumulate to a lethal threshold. As an emerging therapeutic strategy, sonodynamic therapy (SDT) is particularly suitable for deep-seated tumors due to the excellent tissue penetration capabilities of ultrasound (US). Nevertheless, current sonosensitizer typically experience limited sonodynamic efficacy and inadequate targeting of tumors, whereas small interfering RNA (siRNA) presents a highly promising option for gene therapy, its efficacy is heavily dependent on efficient and safe cellular delivery vectors. Therefore, we designed and synthesized a folate-modified Fe-TCPP metal-organic framework (FTFA) nanoplatform that serves both as a siATAD3A gene therapy carrier and as a sonosensitizer to generate ROS upon ultrasound (US) irradiation. ATAD3A displays high expression levels in TNBC and is linked to a negative prognosis; it's silencing reduces MMPs and increases ROS-induced apoptosis. siATAD3A was loaded onto FTFA to prepare FTFA@siATAD3A, which was delivered to TNBC cells via folate receptor-mediated targeting. Under US irradiation, the Fe3+ loaded within this platform synergistically triggers a ferroptosis cascade involving the Fenton reaction, lipid peroxidation, and GPX4 downregulation, effectively inducing ferroptosis. This method greatly reduces the proliferation of cells, as well as their migration and tumor growth when tested in living organisms, and it also shows excellent compatibility with biological tissues. In summary, FTFA@siATAD3A provides a novel strategy for the synergistic gene-ferroptosis therapy of TNBC using sonodynamic effects.